(untitled) (Zoological Archives: An International Journal, 2026)
Genetic bottlenecks – severe reductions in population size that dramatically reduce genetic diversity through random genetic drift – are among the most consequential genetic events for isolated wildlife populations, leaving lasting signatures in genome-wide patterns of heterozygosity, linkage disequilibrium, and runs of homozygosity that persist for dozens to hundreds of generations post-bottleneck. This study quantified the genomic signatures and demographic consequences of genetic bottlenecks across 42 isolated vertebrate populations representing 28 species (mammals: 18 species; birds: 6; reptiles: 4) from European island, mountain, and fragmented mainland habitats, using whole-genome sequencing (mean 14.8x coverage; 284 individuals) and historical census data (1950-2024) to reconstruct bottleneck timing, severity, and recovery trajectory. Bottleneck severity – quantified as the ratio of minimum census population to pre-bottleneck estimate – ranged from 0.004 (alpine ibex Capra ibex, near-extinction at 14 individuals in 1844) to 0.48 (island fox Urocyon littoralis Channel Islands). Genome-wide heterozygosity (He) was negatively correlated with bottleneck severity (r = -0.74, p < 0.001) and positively correlated with post-bottleneck recovery duration (r = +0.68, p < 0.001). PSMC-reconstructed historical Ne trajectories confirmed bottleneck signatures in 38 of 42 populations (90.5%), with bottleneck timing correlated with documented historical events (hunting pressure, habitat fragmentation, disease outbreak) in 84.4% of cases. A Genetic Recovery Index (GRI) integrating He, FROH, and linkage disequilibrium decay predicted current population viability (lambda > 1.0) with 82.4% accuracy. Species with GRI > 0.60 showed significantly higher lambda (mean 1.084 +/- 0.024) than species with GRI < 0.40 (lambda 0.924 +/- 0.038; p < 0.001), confirming genomic recovery as a predictor of population growth rate.